Analisis Efisiensi Desain Tata Letak Produksi Susu Sapi PT. Waluya Wijaya Farm di Kecamatan Cibinong, Kabupaten Bogor, Jawa Barat - Nurul Nur Fadillah; Hanivatul Husna; Theresa Lidya; Helmi Naufal Azmi; Wawan Oktariza; Tina Nur Ainun (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study analyzes the efficiency of cow's milk production layout design at PT Waluya Wijaya Farm, located in Cibinong District, Bogor Regency, West Java. Given the importance of cow's milk as a source of calcium for bone growth, plant layout efficiency is crucial to improve productivity. Primary data collection methods involved direct observation and interviews, while data analysis used qualitative and quantitative approaches. The two main methods applied were Activity Relationship Chart (ARC) and Total Closeness Rating (TCR). The ARC method helps in planning the layout of factory facilities based on the level of interaction between activities, while TCR evaluates the level of closeness of each department or facility. The results show that the current layout is not yet efficient, with top priority given to the packing cup facility which has the highest TCR value. This study concludes that PT Waluya Wijaya Farm needs a more efficient layout to increase the productivity of pasteurized cow milk production.